Analisis Pendekatan Struktural dalam Cerpen "Rembulan di Mata Ibu" Karya Asma Nadia - Putri Ayu Nengsih; Abdurahman Abdurahman (Journal of Literature Review, 2026)
This study aims to analyze the short story "Rembulan di Mata Ibu" by Asma Nadia using a structural approach. This approach focuses on intrinsic elements such as theme, plot, characterization, setting, point of view, and message. The research employs a descriptive qualitative method with textual analysis through close reading. The results indicate that the main theme of the short story is maternal love hidden behind a strict attitude, along with the inner conflict between a child and her mother. The plot follows a progressive structure with a strong emotional climax. Characterization highlights the psychological development of the main character, while the setting strengthens the emotional atmosphere of the story. The use of the first-person point of view creates a closer emotional connection with the reader. The message conveyed emphasizes the importance of understanding parental love, which is not always expressed directly. Therefore, the structural approach effectively reveals the interrelation of intrinsic elements in constructing the overall meaning of the short story